Restrictions on Impersonal "se" Constructions and Speaker Anchoring - Fábregas, Antonio (2025)
In Spanish, it is often said that impersonal reflexive constructions (e.g., Se vive bien en Lima, 'One lives well in Lima') have no lexical restrictions beyond the requirement that their subjects must be interpreted as human (*Las personas llueven '*People rain' ~ Se llueve '*One rains'). This study identifies two groups of stative verbs that reject the impersonal construction despite allowing human subjects: verbs of relevance and verbs of quantity. The analysis proposes that, in the absence of other c-commanding antecedents, the impersonal se is coreferential with the logophoric center of the utterance, which by default is the speaker. The verbs that reject impersonal se are those that do not accept subjects corresponding to the speaker, for different reasons. This reinterprets the obligatoriness of human readings for the subject, a phenomenon already identified in the literature, as coming from the fact that speakers are always human.